Performance of artificial antioxidants In RBD Palm Olein during deep-fat frying - Jaswir, Irwandi; Yusoff, Ahmad Badli (IIUM Press, 2011)
A comprehensive srudy on the perfonnance of using combination of artificial antioxidants. which are butylated hydroxianisole (BHA), butylatcd hydroxytoluene (BH1) and tertiary butylaled hydro-xyquinone (TBHQ) acting as synergist during repeated deep_fat frying process of potato chips in refined. bleacbed and deodorised (ROD) palm olein bas been performed. From many recent srudy artificial antioxidanl5. but)'lated hydroxianisole (BHA). butylated hydroxytoluene (BIlT) and tertiary butylated hydroxyquinone (TBHQ) are well known amioxidants that are widely used commercially in food industries. Yet the use of this antioxidants is 1:lcing criticized because its implication to the health. However. Ihe lower COSt of these antioxidants made them applicable to usc for the certain product of food. Determination physico-chemical characteristic combination of these artificial antioxidants will be conducted In this study to ensure the efficacy of this artificial antioxidant in preserving palm olein during deep-fat frying. Optimization study on the efficiency of use the arttficial antioxidants during deep-fat frying was conducted by using 15 combinations of these antioxidants achieved from Echip software. This study successfully de"e1oped general ideals for designing suitable methodology for monitoring quality changes of RBD palm olein with addition of artificial amioxidanls during deep-fat frying. Four important parameter>; for the derennination physico-chemical chat3cteristic of RBD palm olein during deep-fal used In (his study were peroxide value (PV). iodine value (IV) and absorbance at 132nm and 268nm. Results showed that all three artificial antioxidants used have been proven to give significant effects on inhibiting deterioration in RBD palm olein during deep·fat frying. Based on (he result obtained, an optimum combination 112.5 ppm 13HA and 200 ppm of BHT and TBIIQ can be recommended for use in RBD palm olein during deep-fal frying.